Study on Sulfide Layer Attenuation Behavior of Smithsonite During Sulfidization Flotation - Zeng, Yong; Liu, Jian; Dong, Wenchao; Hao, Jiamei; Wang, Yu (Frontiers in Materials, 2020)
The S content on the surface of smithsonite plays a decisive role in smithsonite flotation. In this study, the attenuation behavior of smithsonite surface sulfide layer was investigated by inductive coupling plasma mass-spectrometric (ICP-MS) and X-ray photoelectron spectroscopic (XPS). The results of smithsonite surface S adsorption capacity tests indicated that smithsonite surface sulfide layer is not stable, and the S adsorption capacity decreased from 22.12×10-7 mol/g to 20.52×10-7 mol/g from 6 min to 8 min with a decrease of 7.2%. NH4Cl can enhance the stability of S adsorption on the smithsonite surface. Smithsonite surface S adsorption capacity of sulfidization for 8 min with a increase of 10.9% after adding NH4Cl compared with the absence of NH4Cl. The results of smithsonite surface S falling off capacity tests indicated that the S-species will fall off from smithsonite surface under mechanical stirring, which largest amount of S falling off capacity is 3.701×10-7 mol/g, with a decrease percentage of 16.7%. X-ray photoelectron spectroscopic (XPS) analysis was used to investigate the chemical compositions, elemental chemical states of S-species of falling off. The results indicated that monosulfide, disulphide, polysulph, sulphite and sulphate are all the sources of the falling off of S-species, and the relative content in smithsonite samples of disulphide has the greatest decreasing, reaching 0.33%. Mechanical stirring is an important reason for sulfide layer attenuation of smithsonite surface. Monosulfide, disulphide and polysulph on smithsonite surface can be converted into soluble sulphite and soluble sulphate, resulting in the decrease of S content on smithsonite surface.